2020
DOI: 10.1021/acs.jcim.0c00599
|View full text |Cite
|
Sign up to set email alerts
|

Generative Network Complex for the Automated Generation of Drug-like Molecules

Abstract: Current drug discovery is expensive and time-consuming. It remains a challenging task to create a wide variety of novel compounds that not only have desirable pharmacological properties but also are cheaply available to low-income people. In this work, we develop a generative network complex (GNC) to generate new drug-like molecules based on the multiproperty optimization via the gradient descent in the latent space of an autoencoder. In our GNC, both multiple chemical properties and similarity scores are opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 53 publications
1
108
0
5
Order By: Relevance
“…The design of target chemical libraries is actually an undertaking of increasing interest, as illustrated by a number of recent studies that have reported the implementation of artificial intelligence-based algorithms [ 63 , 64 , 65 , 183 , 184 , 185 , 186 ]. One of them is the development of ReLeaSE (Reinforcement Learning for Structural Evolution), which integrates a generative deep neural network with a predictive one into a joint framework for the design of novel compounds satisfying certain chemical requirements, as illustrated with the biased selection of compounds fulfilling a specific range of physical properties (i.e., melting temperature and lipophilicity) or inhibitory activity against the desired target protein (Janus protein kinase 2) [ 62 ].…”
Section: Exploiting Chemical Libraries and Biological Datamentioning
confidence: 99%
“…The design of target chemical libraries is actually an undertaking of increasing interest, as illustrated by a number of recent studies that have reported the implementation of artificial intelligence-based algorithms [ 63 , 64 , 65 , 183 , 184 , 185 , 186 ]. One of them is the development of ReLeaSE (Reinforcement Learning for Structural Evolution), which integrates a generative deep neural network with a predictive one into a joint framework for the design of novel compounds satisfying certain chemical requirements, as illustrated with the biased selection of compounds fulfilling a specific range of physical properties (i.e., melting temperature and lipophilicity) or inhibitory activity against the desired target protein (Janus protein kinase 2) [ 62 ].…”
Section: Exploiting Chemical Libraries and Biological Datamentioning
confidence: 99%
“…The use of CADD algorithms and tools could reduce drug development costs and time significantly with conservative estimates suggesting AI pipelines require less than 1/3 of the current time and cost [152,153]. Examples of DRL-based de novo drug design include the development of adenosine A2A receptor ligands [83], rapid identification of potent DDR1 kinase inhibitors [154], and the development of a large number of new BACE1 inhibitors, which is an enzyme involved in Alzheimer's disease [118].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the latent vector is an intermediate representation containing the "meaning" of the input sequence. In the case of de novo drug design, the input and output sequences are both SMILES strings [118]. A generative network complex was successful in generating new drug-like molecules based on multi-property optimization via a gradient descent in the latent space of an autoencoder [118].…”
Section: Sequence-to-sequence Autoencoder (Seq2seq Ae)mentioning
confidence: 99%
See 2 more Smart Citations